Occurrence and Effects on Weaning From Mechanical Ventilation of Intensive Care Unit Acquired and Diaphragm Weakness: A Pilot Study - Bertoni, Michele; Piva, Simone; Beretta, Alessandra; Bongiovanni, Federica; Contarino, Riccardo; Artigas, Ricard Mellado; Ceresoli, Lucia; Marchesi, Mattia; Falappi, Michele; Belleri, Marta; Goffi, Alberto; Pozzi, Matteo; et al. (Frontiers in Medicine, 2022)
Purpose Limb intensive care unit (ICU)-acquired weakness (ICUAW) and ICU acquired diaphragm weakness (DW) occur frequently in mechanically ventilated (MV) patients; their coexistence in cooperative and uncooperative patients is unknown. This study was designed to (1) describe the co-occurrence of the two conditions (2) evaluate the impact of ICUAW and DW on the ventilator-free days at 28 days and weaning success, and (3) assessed the correlation between MIP and TFdi in patients with DW. Methods This prospective pilot study was conducted in a single-center on 73 critically ill mechanically ventilated patients. Muscle weakness was defined as a Medical Research Council (MRCss) score < 48 in cooperative patients or a bilateral mean simplified peroneal nerve test (PENT) <5.26mV in uncooperative patients. Diaphragm dysfunction was defined as maximal inspiratory pressure (MIP) < 30 cmH2O or as a thickening fraction (TFdi) <29%. Weaning success was defined according to WIND (Weaning according to a New Definition). Results: Fifty-seven patients (78%) had ICUAW and 59 (81%) had DW. The coexistence of the two conditions occurred in 48 patients (65%), without association (χ2=1.06, p=0.304). In the adjusted analysis, ICUAW was independently related to VFDs at 28-days (estimate difference 6 days, p= 0.016), and WIND (OR of 3.62 for having WIND different than short weaning), whereas DW was not. The linear mixed model showed a significant but weak correlation between MIP and TFdi (p<0.001) Conclusions: This pilot study is the first to explore the coexistence of ICUAW and DW in both cooperative and uncooperative patients; a lack of association was found between DW and ICUAW when considering both cooperative and uncooperative patients. We found a strong correlation between ICUAW but not DW with the VFDs at 28 days and weaning success. A future larger study is warranted in order to confirm our results, and should also investigate the use of transdiaphragmatic twitch pressure (PdiTw) measurement during bilateral anterior magnetic phrenic nerve stimulation (BAMPS) for the diagnosis of DW.